Pengaruh Membaca Alquran terhadap Kestabilan Emosi pada Mahasiswa di Bukittinggi - Ikhsan, Alfi Khairul; Akbar, Zidan Maliki; Oktari, Dela; Dira, Laura Farah; Andini, Juwita Putri; Fitra, Ilham; Alwi, Muhammad Habib (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2025)
This research aims to examine the effect of reading the Koran on the emotional stability of students in Bukittinggi. This research approach is quantitative with a causal design with regression analysis methods. The sample used was 122 students selected at simple random. The results of the analysis show that there is a significant influence between reading the Koran and students' emotional stability. There is a value of 10.9% indicating that reading the Koran contributes to emotional stability. This research supports previous findings that reading the Koran has a positive impact on mental health and emotional stability.